Virulence gene landscapes of Salmonella in Eastern and Southern Africa - Mohamed, Mohamed-Yousif Ibrahim; Habib, Ihab (Frontiers in Microbiology, 2025)
Salmonellosis is one of the main foodborne diseases in Eastern and Southern Africa, however its different forms are not fully understood. Based on studies conducted over 20 years, the review discusses how invA, the spv operon, the cdtB-pltAB typhoid toxin cassette, the adhesion factor bapA, and loci related to stress responses (pagC, mgtB) affect pathogenic strains isolated from livestock, wildlife, produce, and humans from various countries. Findings reveal pronounced ecological and geographic variation, S. Typhimurium and S. Enteritidis in Ethiopia's dairy chain and Tanzanian backyard poultry carry spv at rates exceeding 80%, while whole-genome studies from South Africa document the continent's most extensive accessory-gene repertoires and identify fully virulent strains in reptiles and market vegetables. Human outbreaks mirror this diversity, Nairobi pediatric isolates harbor universal hilA/sopB and Stn; Ugandan epidemics rely on chromosomal factors despite minimal spvB; Rwandan Moero serovars uniquely possess the cytolethal-distending-toxin cassette. Altogether, the data suggests a significant need for syncing genomic disease surveillance with the One-Health approach, this will allow for early detection of hybrid and migrating bacteria, shielding children, serious disease sufferers, and those serving the food sector against more spread of dangerous pathogens.